THE IMPLEMENTATION OF SCIENTIFIC APPROACH WITH GROUP SETTING TO IMPROVE THE 11TH GRADE SCIENCE 6 STUDENTS’ MATHEMATICAL CRITICAL THINKING SKILLS AT SMAN 22 BANDUNG IN THE LEARNING OF DERIVATIVES AND ITS APPLICATIONS - Nana Sukarna; Nur Iman ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This study was conducted under the action research method. It aims to analyse the role of scientific approach to Mathematical Critical Thinking (MCT) skills of high school students. This study was conducted in SMAN 22 Bandung and involved 31 students from grade XI Science 6 as participants and three essays of MCT test as the instruments. This study was conducted in three cycles. The researcher found that there was an improvement on the students’ MCT skills from cycle to cycle. The students encountered difficulties in solving problems related to identifying relevant and irrelevant data; hence, they did not encounter any difficulties in examining the validity of the process.